P0236COMPARISON OF THE CHARACTERISTICS AND SEVERITY OF RESTLESS LEG SYNDROME AND INSOMNIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE AND RENAL TRANSPLANT RECIPIENTS. (6th June 2020) - Pappa, Maria; Pappas, Haralambos; Kokkolou, Elisabeth; Aimilios, Andrikos; DUNI, ANILA; Rapsomanikis, Karolos Pavlos; Balafa, Olga; Dimakopoulos, Georgios; Steiropoulos, Paschalis; Pnevmatikos, Ioannis; Konstantinidis, Athanasios; Mitsis, Michalis; et al.
Abstract: Background and Aims: Symptoms of restless legs syndrome (RLS) are common in patients with chronic kidney disease (CKD) and on dialysis, affecting up to 25% of patients when the international RLS diagnostic criteria are applied. RLS has been associated with disordered sleep, impaired quality of life, increased cardiovascular morbidity and mortality risk in patients with CKD. The aim of our study was to examine the relationship between RLS and the prevalence and severity of insomnia in non-dialysis CKD patients (CKD stage IV and V), in haemodialysis and PD patients, in renal transplant recipients (RTRs) as well as to identify the risk factors independently associated with RLS prevalence and severity in each group. Method: 436 patients were included in the study (152 patients with CKD stage IV and V, 117 haemodialysis patients, 78 PD patients and 89 RTRs). RLS diagnosis was made according to IRLSSG diagnostic criteria. The questions of the IRLSSG Severity Scale were answered. Athens Insomnia Scale (AIS) was used for the diagnosis of insomnia. Statistical analysis was performed with appropriate parametric and non-parametric tests and regression analysis models. Results: Applying the IRLSSG criteria for diagnosis, the prevalence of RLS was 17%, 25.9%, 26.5%, 32.1% and 16.9% in patients with CKD stage IV, CKD stage V, hemodialysis patients, PD patients and RTRs respectively. The mean severity of the syndrome was higher in PD patients (14.64), followed by haemodialysis patients (12), CKD stage V patients (11.9), KTRs (11.3) and patients with CKD stage IV patients (10.5). Prevalence of RLS did not significantly differ between groups. CKD patients displayed the lowest presence of insomnia, while PD patients showed the relatively highest presence of insomnia. The mean severity of insomnia differed between the pairs: RTRs vs PD patients, RTRs vs haemodialysis patients and PD patients vs patients with CKD stage IV and V (p <0.05). RLS in all groups correlated with the presence of peripheral neuropathy and female gender. By regression analysis models we found that among CKD patients, presence of RLS independently correlated with number of pregnancies in women, previous cerebrovascular disease, hypothyroidism requiring treatment and antidepressant drugs use, whereas RLS severity independently correlated with the presence of peripheral neuropathy. Regarding hemodialysis patients, presence of RLS independently correlated with body mass index (BMI), female gender, antidepressant drugs use and serum PTH levels. RLS severity in the same group independently correlated only with female gender. Regarding PD patients, RLS presence was independently associated with number of pregnancies in women and left ventricular ejection fraction. RLS severity in the same group was independently associated only with the presence of peripheral arterial disease. Among RTRs, RLS presence independently correlated with female gender and a lower GFR. We were the first to find that presence of RLS was associated with a higher bone mass density and lower levels of 25-OH vitamin D. Conclusion: The prevalence and severity of RLS and insomnia worsen as kidney function deteriorates in CKD patients, being most burdensome among patients with stage V CKD, haemodialysis and PD patients. The severity of insomnia is especially increased in PD patients. Although the frequency of RLS decreases in KTRs, it still occurs at higher rates compared to the general population. Further studies are needed to investigate the relationship between RLS and associated risk factors in patients with CKD and following kidney transplantation.